Revitalizing Shame as a Moral Fortress for the Young Generation in the Digital Era: An Analysis of Decadence and a Strategic Framework for Moral Preservation - Yanti Novita; Fitri Wahyuningsing; Syafruddin; Zulhendi; Rehani (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the phenomenon of the decadence of al-ḥaya' (sense of shame) values ​​in the younger generation amidst the massive flow of digital modernity and to formulate a comprehensive strategic framework for the preservation of Islamic morals in the virtual space. With a qualitative approach of Library Research , data were collected through documentation techniques and systematic recording from primary sources (religious texts and scientific journals) and secondary sources (KPAI and APJII reports), then analyzed using Qualitative Content Analysis . The results of the study indicate that the decline of al-ḥaya' values ​​which function as syu'batun min al-iman (a branch of faith) is mainly triggered by a spiritual crisis (deficit in the concept of ihsan ) and the dominance of digital media that normalizes excessive self-disclosure behavior , erodes awareness of Divine supervision ( muraqabah ), and weakens self-control. Therefore, a Comprehensive Strategic Framework was formulated that focuses on the synergy of three educational centers: the integration of al-ḥaya' in the curriculum through habituation ( ta'wid ) and role modeling ( qudwah ḥasanah ) in schools, revitalization of the family ecosystem through parental digital role models, and strengthening Islamic value-based digital literacy. This study confirms that this holistic approach is effective in reactivating al-ḥaya' as an optimal self-regulation mechanism , providing practical and theoretical contributions to ensuring Muslim integrity and the preservation of morals in both physical and virtual public spaces.